Dynamics of Choice: A Tutorial - Baum, William M (Society for the Experimental Analysis of Behavior, Inc, 2010)
Choice may be defined as the allocation of behavior among activities. Since all activities take up time, choice is conveniently thought of as the allocation of time among activities, even if activities like pecking are most easily measured by counting. Since dynamics refers to change through time, the dynamics of choice refers to change of allocation through time. In the dynamics of choice, as in other dynamical systems that include feedback, change is away from perturbation and toward a steady state. Steady state or equilibrium is assessed on a longer time scale than change because change is only visible on a smaller time scale. When we compare laws of equilibrium, such as the matching law with laws of dynamics, two possibilities emerge. Self-similarity occurs when the same law can be seen across smaller time scales, with the result that the law at longer time scales may be understood as the expression of its application at smaller time scales. Reduction occurs when the dynamics at a small time scale are incommensurate with the dynamics at longer time scales. Then the process at the longer time scale is reduced to a qualitatively different process at the smaller time scale, as when choice is reduced to switching patterns. When reduction occurs, the dynamics at the longer time scale may be derived from the process at the smaller time scale, but not the other way around. Research at different time scales is facilitated by the molar view of behavior.